Gersonides' afterlife : studies on the reception of Levi ben Gerson's philosophical, Halakhic and scientific oeuvre in the 14th through 20th centuries - Elior, Ofer; Freudenthal, Gad; Wirmer, David; Leicht, Reimund; Université de Genève (Leiden ; Boston : Brill, 2020)
"Gersonides' Afterlife is the first full-scale treatment of the reception of one of the greatest scientific minds of medieval Judaism: Gersonides (1288-1344). An outstanding representative of the Hebrew Jewish culture that then flourished in southern France, Gersonides wrote on mathematics, logic, astronomy, astrology, physical science, metaphysics and theology, and commented on almost the entire bible. His strong-minded attempt to integrate these different areas of study into a unitary system of thought was deeply rooted in the Aristotelian tradition and yet innovative in many respects, and thus elicited diverse and often impassionate reactions. For the first time, the twenty-one papers collected here describe Gersonides' impact in all fields of his activity and the reactions from his contemporaries up to present-day religious Zionism"--
Part 1. The reception of Gersonides' philosophical and Halakhic oeuvre. "Composition, not commentary" : Gersonides' commentary on the Isagoge of Porphyry and its afterlife / Charles H. Manekin -- The supercommentaries of Gersonides and his students on Averroes's epitomes of the Physics and the Meteorology / Steven Harvey and Resianne Fontaine -- Crescas' relationship to Gersonides / Warren Zev Harvey -- From denunciation to appreciation : Gersonides in the eyes of members of the Ibn Shem Ṭov family / Doron Forte -- Gersonides and his Sephardic critics / Seymour Feldman -- A fifteenth-century reader of Gersonides : Don Isaac Abravanel, providence, astral influences, active intellect, and humanism / Cedric Cohen-Skalli and Oded Horezky -- Gersonides' philosophy in fifteenth-century Byzantium : Shabbetai ben Malkiel ha-Kohen's defense of Averroes's theory of material intellect / Ofer Elior -- Gersonides' reception in the Ashkenazi yradition / Tamás Visi -- The Karaite reception of Gersonides / Daniel J. Lasker -- Gersonides' Biblical commentaries in a fifteenth-century Slavic translation of the Bible / Moshe Taube -- Gersonides' responsa and their reception / Pinchas Roth -- Part 2. The reception of Gersonides' astronomical and astrological oeuvre. The lunar cycle of 11,325 Days / José Chabás and Bernard R. Goldstein -- The afterlife of Gersonides' cross-staff and of the poem dedicated to it / Gad Freudenthal -- Violas de Rodez' political prognostication for the year 1355 : reaction to the prognostications for 1345-1355? / Hagar Kahana-Smilansky -- Part 3. Printing and Reading Histories. The reception history of Gersonides' writings, according to their early printing history (fifteenth-sixteenth centuries) / Zeev Gries -- Gersonides Hebraicus atque Latinus : some remarks on Levi ben Gershom's works and the reading and book-collecting cultures of the Renaissance / Michela Andreatta -- Censoring/"improving" Gersonides : the case of the Toʻalot / Menachem Kellner -- Part 4. Gersonides' oeuvre in nineteenth-century Germany. Rabbi Abraham Nager and Ludwig Philippson -- the revisor and sponsor of the Leipzig edition of Gersonides' Milḥamot Ha-Shem (1866) : the Wissenschaft des Judentums and Orientalistik in nineteenth-century Germany (a case study) / Gad Freudenthal -- The rediscovery of Gersonides as a religious philosopher by the Wissenschaft des Judentums (1860-1890) / George Y. Kohler -- Benzion Kellermann's German translation of Gersonides' Milḥamot ha-Shem (1914-1916) : the history of a scholarly failure / Torsten Lattki -- Part 5. Late repercussions of Gersonides' oeuvre. Notes on Gersonides' place in religious-Zionist thought / Dov Schwartz.
Papers from a conference held 17-19 February 2014 at the University of Geneva.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on April 01, 2022).
eBooks on EBSCOhost
Keywords: Levi ben Gershom, -- 1288-1344 -- Influence -- Congresses; Levi ben Gershom, -- 1288-1344 -- Congresses; Levi ben Gershom, -- 1288-1344; Jewish philosophy -- To 1500 -- Congresses; Jewish philosophy -- Congresses; Philosophie juive -- Jusqu'à 1500 -- Congrès.; Philosophie juive -- Congrès.; Influence (Literary, artistic, etc.); Jewish philosophy; To 1500; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.